Learning by Doing and Learning from Others: Human Capital and Technical Change in Agriculture - Foster, Andrew D.; Rosenzweig, Mark R. (Journal of Political Economy, 1995)
Household-level panel data from a nationally representative sample of rural Indian households describing the adoption and profitability of high-yielding seed varieties (HYVs) associated with the Green Revolution are used to test the implications of a model incorporating learning by doing and learning spillovers. The estimates indicate that (i) imperfect knowledge about the management of the new seeds was a significant barrier to adoption; (ii) this barrier diminished as farmer experience with the new technologies increased; (iii) own experience and neighbors' experience with HYVs significantly increased HYV profitability; and (iv) farmers do not fully incorporate the village returns to learning in making adoption decisions.